Face-To-Face, Blended, Hybrid, and Online Instructional Delivery Methods: a Comparative Study of English Language Learners’ Grades in a Mathematics Course in a Higher Education Institution in the United Arab Emirates. - Brashear, Lisa (2020)
Advances in technology have made different instructional delivery methods possible. Moreover, due to the recent world pandemic, instruction has shifted to completely online delivery. This comparative quantitative study aims at investigating whether instructional delivery methods (such as online, hybrid, blended learning, and face-to-face delivery methods) had an effect on students’ grades when teaching mathematics to English Language Learners in a Higher Education Institution (HEI) in the United Arab Emirates. Final course grades, in GPA format, of 574 students were collected over the course of three academic years. Assumptions of analysis of variance (ANOVA) were examined. The ANOVA revealed that there was a significant difference in students’ average grades between the different instructional delivery methods. Six comparisons were made: (1) face-to-face versus blended, (2) face-to-face versus hybrid, (3) face-to-face versus online, (4) blended versus hybrid, (5) blended versus online, and lastly (6) hybrid versus online. Postdoc tests showed there were statistically significant mean differences between all six pairwise comparisons. Furthermore, this study used Cohen’s d and Hedges’ g for the pairwise comparisons of the six statistically significant results. The results revealed that (a) students scored statistically significantly lower grades in the face‑to‑face group than in the blended group with a mean difference of 0.72 and an effect size of .47, (b) students in the face‑to‑face group scored statistically significantly lower than the students in the hybrid group, with a mean difference of 1.17 and an effect size of .79, (c) the face‑to‑face group displayed the largest statistically significant mean difference of 2.23 lower than the online group, with a very large effect size of 1.49, which was also the greatest effect size of the study, (d) students scored statistically significantly lower grades in the in the blended group than hybrid group, with a mean different of .45 and an effect size of 0.31, (e) students in the blended group scored lower grades than in the online delivery, with a mean difference of 1.51 and an effect size of 1.05, and (f) the hybrid group scored statistically significantly lower than the online group with a mean difference of 1.06 and an effect size of 0.87. Lastly, eta‑squared (η2), and omega squared (ω2) revealed a medium effect size of nearly 12% of the overall group differences. The study concludes that students in the online method had a significantly higher grade with a large to very large effect size compared to other methods. Further studies can be performed to include students’ grades from other faculty, and other classes in HEI’s. Lastly, qualitative research is recommended to analyze students and instructors’ perspectives on why students perform better online.